The Influence of Brand Image, Brand Trust, and Service Quality on Consumer Purchase Decisions of Pizza Hut Products in Surabaya City, Indonesia - Atmanagara, Muhammad Sulthan As’ad; Purwanto , Sugeng (Golden Ratio of Mapping Idea and Literature Format, 2026)
Pizza Hut, despite being the pizza brand with the highest Top Brand Index in Indonesia, continues to face challenges such as declining consumer purchasing power and boycott movements that have affected its sales and workforce. This study aims to analyze the influence of brand image, brand trust, and service quality on consumer purchase decisions of Pizza Hut products in Surabaya. It tests the hypothesis that these three variables have a positive and significant effect. A quantitative approach was employed by distributing online questionnaires via Google Forms to 112 residents of Surabaya who had purchased Pizza Hut products, utilizing convenience sampling for accessibility and relevance. The sample size was considered adequate for Partial Least Squares Structural Equation Modeling (PLS-SEM), which was used to analyze the relationships among the variables. The findings indicate that brand image, brand trust, and service quality all have a positive and significant influence on consumer purchase decisions, highlighting the importance of these factors in strengthening Pizza Hut's marketing strategy amid market challenges.